Human Development and the Catholic Social Tradition Towards an Integral Ecology - Deneulin, Severine (Taylor & Francis, 2021)
This book brings development theory and practice into dialogue with the religious tradition, in order to construct a new, trans-disciplinary vision of development, with integral ecology at its heart. It focuses on the Catholic social tradition and its conception of integral human development on the one hand, and on the works of economist and philosopher Amartya Sen which underpin the human development approach on the other. The book discusses how these two perspectives can mutually enrich other around three areas: their views on the concept and meaning of development and progress; their understanding of what it is to be human, that is, their anthropological vision; and their analysis of transformational pathways for addressing social and environmental degradation. The book examines how both human development and the Catholic social tradition can function as complementary analytical lenses and mobilizing frames for embarking on the journey of structural and personal transformation to bring all life systems, human and non-human, back into balance. This book is written for researchers and students in development studies, theology, and religious studies, as well as professional audiences in development organisations.